With Love and Kisses: Nothing Lasts Forever: An Examination of the Social and Artistic Antiquation of Moral Rights. Issue 3 (18th October 2016) - Lewis, Jessica
Abstract: This article examines the social and artistic antiquation of moral rights law. Moral rights law developed, and was implemented, under the heavy influence of the French preference to put the rights of the author at the center of intellectual property protection (with Victor Hugo leading this charge). However, as artistic practice evolves in a continually rapid fashion, it is becoming increasingly clear that moral rights are unable to properly accord with modern art forms. An examination of the social construction of authorship, the emergence of unique contemporary art forms, and the role of technology as a catalyst to intellectual property law, reveals that the Western world's legal moral rights scheme cannot survive its current form. Moral rights' endurance hinges on its ability to reconcile with a social and artistic climate alien to its origins. Artistic expression does not exist in a vacuum and is inextricably linked to, and reflective of, the social climate it is born out of. As society evolves and shifts, so too does its art and so must the law.